The Role of Personality Factors on Job Satisfaction among Academic Staff at Public Research University - Aida Mehrad, Hanina Halimatussadiah Ma’rof Bin Redzuan, Haslinda Abdullah (Journal of Educational, Health and Community Psychology, 2015)
Abstract The current study was intended to examine the association between personality factors and job satisfaction among academic staff. The job satisfaction assumed as an essential factor in educational organizations spatially university that influenced by various factors. Moreover, distinguishing these effective factors is very important and lack of consideration to this inner feeling leads to several abnormal organizational behaviors at university. Therefore, this study focused on the association between these two factors at university. A cross-sectional examination design was applied with purposive selected sample that taken from academic staff (N=440) of public research universities in Klang Valley, Malaysia. In present study, the participants completed the job descriptive index inventory and the big five personality test which explained their personality factors and their relation with job satisfaction. It is concluded that neuroticism as one of the main personality factors predicts job satisfaction and there is negative relationship between neuroticism and job satisfaction and also there are positive relationships between agreeableness, consciousness and openness with job satisfaction that analyzed by correlation coefficient and regression analysis test. Key word: personality factors, job satisfaction, academic staff, university